The effect of lead acetate on oxidative stress and antioxidant status in rat bronchoalveolar lavage fluid and lung tissue. (July 2013) - Samarghandian, Saeed; Borji, Abasalt; Afshari, Reza; Delkhosh, Mohammad Bagher; gholami, Ali
Abstract Despite the wide spread of lead environmental pollution, the effect of this heavy metal on respiratory disease was not shown yet. In respect to increased oxidative stress is an important mechanism in the pathogenesis of respiratory disease, the present study was designed to examine the association between lead toxicity and lung disease via measuring oxidative stress biomarkers in bronchoalveolar lavage fluid (BALF) and lung tissue of rat. For this aim, 32 rats were divided into the following groups of eight animals each: control, three lead tested (received lead acetate in the drinking water for a period of 14 d at concentrations of 250, 500 and 1000 ppm) groups. At the end of the 2 week period, malondialdehyde (MDA), nitric oxide (NO) and reduced glutathione (GSH) contents were measured to assess free radical activity in the BALF and lung tissue. Superoxide dismutase (SOD) was also determined. A significant dose-dependent increase in the BALF supernatant and lung homogenate levels of MDA and NO with decrease GSH level and SOD activity were observed in the lead-treated groups compared with the control group (p < 0.05). Thus, lead acetate may be contributed to respiratory disorders via increased oxidative stress.